Application of High Performance Liquid Chromatography to the Analysis of Pesticide Residues in Apple Juice - Velkoska-Markovska, Lenche; Petanovska-Ilievska, Biljana; Markovski, Aleksandar (Walter de Gruyter GmbH, 2018)
The modern apple production involves the use of large amounts of pesticides that can be found in processed products such as apple juice. Harmful effects of pesticide residues on humans, especially children, are well known, hence the content of pesticide residues in fruit, vegetables and their juices should be controlled. This study presents an application of a new, relatively simple and reliable analytical method for qualitative and quantitative determination of three organophosphorus and one organonitrogen pesticide residues in apple juices. The analysis utilizes reversed-phase high-performance liquid chromatography (RP-HPLC) followed by UV diode array detection. Prior to HPLC analysis, a solid-phase extraction (SPE) was used for analytes concentration and sample clean-up. Specificity, selectivity, linearity, precision, accuracy and limit of quantification (LOQ) were examined to assess the validity of the developed method. The method had satisfactory values of multiple correlation coefficients for calibration curves (R2 ≥ 0.95 ). The precision was evaluated for the retention times and peak areas, and the estimated values for relative standard deviations (RSD) were 0.05 % - 0.18 % and 0.09 % - 0.62 %, respectively, which indicated an excellent precision of the proposed method. Under the established conditions, the recovery of analytes was 93.80 % - 119.41 %, with relative standard deviations below 0.56 %. This method was successfully applied for determination of some organophosphorus and organonitrogen pesticide residues in apple juices which were taken from Macedonian markets. The achieved values for LOQs were low enough compared to the MRLs of the investigated pesticides in apple according to the Regulation (EC) No 396/2005. Detectable residues of the examined pesticides were not found in the analyzed samples.